Should Electoral Cycles Disappear? - Caleiro, António Bento (2019)
This note states that a positive response to the question: “Should electoral cycles disappear?”, is not (necessarily) desirable when politicians do not even care about the upcoming elections because a single - the current - mandate is sufficient to achieve their (ideological) intentions of (strictly) private/personal nature.